Child passenger safety training for healthcare professionals in Singapore - Ronald Ming Ren Tan; Shelly-Anne Sherwood; Nirmal V Kavalloor; Jasmine XY Feng; Arif Tyebally; Shu-Ling Chong (Annals of the Academy of Medicine, Singapore, 2022)
annals-acadmedsg.2022169Road traffic injuries are a preventable cause of childhood morbidity and mortality.1,2 Use of age-appropriate child car seats (CCS) lowers the risk of injury and death by about 82% and 28%, respectively.3-5 In Singapore, although the Road Traffic Act states that CCS use is mandatory,6 many children presenting to paediatric emergency departments are unrestrained at the time of the road traffic accident.